177 A severe cytokine release syndrome with respiratory failure in recurrent mesothelioma induced by EpCAM CAR-T cells infusion: a case report. (10th December 2020) - Wang, Sitong; Fang, Juemin; Wang, Hui; Xu, Qing
Abstract : Background: With the development and maturity of chimeric antigen receptor T (CAR-T) cells therapy-related technologies, the application of CAR-T therapy has progressed from blood tumors to solid tumors, and its potential risks and side effects have been more widely recognized. As the most common complication of CAR-T therapy, cytokine release syndrome (CRS) is an inflammatory syndrome caused by the activation and proliferation of T-cell and the increased levels of multiple cytokines. Epithelial cell adhesion molecule (EpCAM) is overexpressed in a variety of tumors and has been used as one of the targets of CAR-T therapy. Case reports of severe CRS due to the use of anti-EpCMA CAR-T cell therapy are very rare. Methods: A 45-year-old malignant mesothelioma woman with EpCAM-positive whose disease progressed after chemotherapy was enrolled into our study (ChiCTR2000030274). The patient received a total of 1.8×107 autologous T cells which contained sequences encoding single-chain variable fragments (scFv) specific for EpCAM after cyclophosphamide lymphodepletion. After the infusion of CAR-T cells, the patient developed typical CRS reactions such as fever, hypoxemia, pulmonary edema, and elevated inflammatory factors. The patient's condition did not improve after the use of anti-inflammatory and antipyretic drugs. After administration of tocilizumab (4 mg/kg, day 6 and day 17) combined with glucocorticoid (40 mg q12h, decreasing gradually), the patient's general condition gradually improved, and chest computed tomography (CT) showed that pulmonary edema was absorbed. Results: The patient's CRS was successfully eliminated after the use of IL-6 inhibitor tocilizumab combined with glucocorticoid. Conclusions: Although EpCAM CAR-T is safe in general, serious complications still happen possibly requiring close monitoring and timely treatment. Our findings suggest that tocilizumab combined with glucocorticoid can be an effective therapeutic method for severe CRS caused by CAR-T cells therapy in solid tumor.